PENGARUH KUALITAS PELAYANAN DAN CITRA MEREK TERHADAP KEPUASAN PELANGGAN PADA SEWA MOBIL DI CV. TEPAT TRANS DI KABUPATEN SIDOARJO - Pratama, Nugroho Adhytiya; Aminah, Siti; Soebintoro, Ugy (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
The purpose of this study was to determine the effect of service quality and brand image on customer satisfaction CV. Exactly Trans Sidoarjo Variable measurement scale has been carried out using an ordinal scale. The population in this study were customers of CV. Exactly Trans Sidoarjo for the period January - December 2020. The sampling method uses a random sampling method with a sample that has been determined by the researcher, with a total of 77 respondents. The model used in this research is SEM-PLS. Based on the test, it can be taken as follows: Service quality has a significant effect on customer satisfaction and Brand Image has a non-significant effect on customers.